Complete Mapping of Thermodynamic Stability of Ternary Oxide SrTiO3 (001) Surface at Finite Temperatures - Md Mokhlesur Rahman; Sehoon Oh; Puspa Raj Adhikari; Jaichan Lee (Advanced Science)
Abstract The oxide surface structure plays a vital role in controlling and utilizing the emergent phenomena occurring at the interface of nanoarchitecture. A complete understanding of ternary oxide surfaces remains challenging due to complex surface reconstructions in various chemical and physical environments. Here a thermodynamic framework is developed to treat the stability of ternary oxide surfaces with finite temperature and chemical environments. Strontium titanate, as a representative ternary oxide, is used to establish the complete energy landscape of SrTiO3 (001) surface. The complete mapping yields a comprehensive understanding of various stable SrTiO3 surfaces with finite temperature and chemical potential or vapor pressure of the constituents, i.e., Sr (or Ti) metal and oxygen. This treatment also reveals a stable surface unknown yet with SrTi2O3 stoichiometry, which unveils the missing link between numerous previous experimental observations and the current understanding of SrTiO3 surface. Interestingly, the new surface shows an anisotropic surface‐localized metallic state originating from the characteristic surface structure. The findings would provide a viable way to understand ternary oxide surfaces and further utilize SrTiO3 surfaces for oxide nanoarchitectures.